Conference Report: 'Less is More'': defining modern bioanalysis. (March 2012) - Dijksman, Jessica; Timmerman, Philip; Abbott, Richard; Barroso, Begona; Kloeppel, Margarete Brudny; Companjen, Arjen; Golob, Michaela; Gordon, Ben; Herling, Christian; Knutsson, Magnus; Luedtke, Silke; Rasmussen, Birgitte Buur; et al.
The 4th Open Symposium of the European Bioanalytical Forum entitled 'Less is More'' was held on 16–18 November 2011 at the Hesperia Tower Hotel, Barcelona, Spain. More than 50 interesting presentations were delivered covering areas with interest for the small- and large-molecule community – biomarker validation; regulations, including an update on new and emerging guidelines and on Global harmonization; technology updates; incurred sample stability; microdosing; dried blood spots and microsampling; challenges of 'free'' and 'total'' macromolecule quantification; stability issues in ligand binding assays or anomalous results. In excess of 450 delegates from more than 170 institutes and companies (industry, regulators and academia) from all global regions participated in the open and stimulating discussions. This manuscript provides an overview of the highlights discussed at the meeting.